Effect of metformin on human periodontal ligament stem cells cultured with polydopamine‐templated hydroxyapatite. (24th April 2019) - Yang, Zun; Gao, Xiang; Zhou, Mengjiao; Kuang, Yunchun; Xiang, Mingli; Li, Jie; Song, Jinlin
Abstract : Polydopamine‐templated hydroxyapatite (tHA) is a type of nano‐biomaterial that can promote osteogenesis in bone tissue engineering. However, high concentrations of tHA stimulate production of reactive oxygen species (ROS), resulting in cell injury and apoptosis. Metformin has been demonstrated to activate the adenosine monophosphate‐activated protein kinase (AMPK) signaling pathway, which induces autophagy and decreases ROS production to prevent apoptosis. The present study was performed to investigate the potential application of tHA in combination with metformin in periodontal bone tissue engineering. Human periodontal ligament stem cells (hPDLSCs) were exposed to tHA in the presence or absence of metformin, and cytocompatibility and osteogenesis were detected by related assays. Additionally, the autophagy signaling pathway was analyzed by western blotting. Polydopamine‐templated hydroxyapatite, in combination with metformin, substantially reduced ROS production and apoptosis, and enhanced proliferation and osteogenic differentiation of hPDLSCs. Enhanced levels of microtubule‐associated protein 1 light chain 3 II and Beclin‐1 were observed after exposure to tHA plus metformin. Expression of phosphorylated AMPK was increased and that of phosphorylated mammalian target of rapamycin (mTOR) was decreased after exposure to tHA plus metformin. Taken together, our results demonstrate that tHA, combined with metformin, increases the viability of hPDLSCs via the AMPK/mTOR signaling pathway by regulating autophagy and further improving the osteogenic effect.